VERBAL FACE THREATENING ACTS USED BY RUBEUS HAGRID IN HARRY POTTER AND THE SORCERER’S STONE MOVIE - Agnes Martil Sianti; I Made Perdana Skolastika (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Language is one of the communication tools used by everyone in interacting with other people. Every word spoken by a language speaker has meaning and purpose, either directly or indirectly. Any expression that belongs to a face-threatening act, whatever it may be and goes against the wishes of the speaker's face, and any part of the speech is considered a face-threatening act. Pragmatics is a strategy to analyze what is the purpose of understanding speech, in pragmatics, there is politeness to knowing how people express negative and positive faces. When people talk to other people, they apply both positive and negative faces in communication to save threatening actions. In this study, Harry Potter and the Sorcerer's Stone analyzed face- threatening actions using the theory of Brown and Levison. In the study aims to determine the verbal face shape used by Rubeus Hagrid in the film. The research procedure is watching a movie or script on youtube, identifying and paying attention to the forms of actions that threaten their faces and classifying positive and negative politeness strategies. The results showed that there are 24 face-threatening actions from 3 forms of threatening actions (actions that threaten the listener's positive face, actions that threaten the listener's negative face, and actions that threaten the speaker's positive) and 4 threatening strategies1)Off –record, 2) Bald on record, 3) negative politeness, 4) positive politeness. For the response of his interlocutor, Rubeus Hagrid often responds to his interlocutor directly. Keywords: Face Threatening Acts, politeness Strategy, Harry potter movie